1999
DOI: 10.1073/pnas.96.22.12887
|View full text |Cite
|
Sign up to set email alerts
|

Survival of reproductive behaviors in estrogen receptor β gene-deficient (βERKO) male and female mice

Abstract: Previously, it was shown that the lack of a functional estrogen receptor (ER) ␣ gene (ER␣) greatly affects reproduction-related behaviors in both female and male mice. However, widespread expression of a novel second ER gene, ER␤, demanded that we examine the possible participation of ER␤ in regulation of these behaviors. In dramatic contrast to our results with ER␣ knockout (␣ERKO) males, ␤ERKO males performed at least as well as wildtype controls in sexual behavior tests. Moreover, not only did ␤ERKO males e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
235
1
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(263 citation statements)
references
References 28 publications
19
235
1
8
Order By: Relevance
“…ER-α knockout male and female mice showed various abnormalities in reproductive aspects, including infertility, no sign of lordosis, and infanticide (Lubahn et al, 1993;Ogawa et al, 1996;Ogawa et al, 1998;Simpson, 1998;Rissman et al, 1999). In contrast, the analyses of reproductive behaviors of ER-β knockout mice indicated the possibility that ER-β is not essential for such behaviors (Krege et al, 1998), since ER-β knockout male and female mice exhibited normal reproductive behaviors (Krege et al, 1998;Ogawa et al, 1999). Taken together, these findings suggest that ER-α, but not ER-β, may be critical to age-related reductions in reproductive function in aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…ER-α knockout male and female mice showed various abnormalities in reproductive aspects, including infertility, no sign of lordosis, and infanticide (Lubahn et al, 1993;Ogawa et al, 1996;Ogawa et al, 1998;Simpson, 1998;Rissman et al, 1999). In contrast, the analyses of reproductive behaviors of ER-β knockout mice indicated the possibility that ER-β is not essential for such behaviors (Krege et al, 1998), since ER-β knockout male and female mice exhibited normal reproductive behaviors (Krege et al, 1998;Ogawa et al, 1999). Taken together, these findings suggest that ER-α, but not ER-β, may be critical to age-related reductions in reproductive function in aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it has been suggested that activation of estrogen receptor-␤ (ER␤)-containing cells may contribute to the termination of sexual behavior (Greco, Blasberg, Kosinski, and Blaustein, unpublished results). Although ER␤ genedisrupted mice show normal sexual behavior, they continue to show sexual behavior considerably longer than do wild-type controls (Ogawa, Chan, Chester, Gustafsson, Korach, and Pfaff, 1999), suggesting that ER␤ is necessary for the normal termination of sexual behavior. Thus, ER␤ may contribute to the termination and/or abbreviation of sexual receptivity.…”
Section: Figmentioning
confidence: 96%
“…Although these data imply distinct functional effects of these receptors, the interaction of these ER subtypes for function is of interest. For example, βERKO mice do not show the same levels of sexual dysfunction as ERα mice demonstrate, and, furthermore, have slightly enhanced sexual receptivity than do their WT counterparts [83]. ERβ-selective phytoestrogens (e.g.…”
Section: The Role Of Erα (And Erβ) For Functional Effects Of Estogensmentioning
confidence: 99%